1988
DOI: 10.1203/00006450-198808000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Glucose Infusion Inhibits Development of β-Receptor Binding in Fetal Lamb Lung

Abstract: ABSTRACT. We used chronic fetal glucose infusion to test the hypothesis that chronic fetal hyperglycemia and hyperinsulinemia inhibit the development of @-receptor binding capapcity (Bmax) in fetal lamb lung. Glucose was infused (14 f 4 mg/kg/h, mean f SD) into eight twin and four singleton fetuses from 112 days gestation until death between 118-145 days gestation. The other eight twins and eleven additional singleton fetuses served as controls. Serum glucose levels were elevated 2-fold and serum insulin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It has been suggested that a link between hyperinsulinemia and RDS may involve a reduction in glycerol-3-phosphate and dihydroxyacetone phosphate production, which impairs surfactant phospholipid synthesis in the lung (54). A further potential mechanism regulating changes in the fetal lung following exposure to hyperglycemia and hyperinsulinemia involves ␤-receptor binding, which plays a vital role in surfactant release and reabsorption of fetal lung liquid (62,64). Interestingly, although the latter study demonstrated a negative impact of hyperglycemia and hyperinsulinemia, similar to that experienced in this study, regarding ␤-receptor binding in the lung, there was a greater effect in males than females (62).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that a link between hyperinsulinemia and RDS may involve a reduction in glycerol-3-phosphate and dihydroxyacetone phosphate production, which impairs surfactant phospholipid synthesis in the lung (54). A further potential mechanism regulating changes in the fetal lung following exposure to hyperglycemia and hyperinsulinemia involves ␤-receptor binding, which plays a vital role in surfactant release and reabsorption of fetal lung liquid (62,64). Interestingly, although the latter study demonstrated a negative impact of hyperglycemia and hyperinsulinemia, similar to that experienced in this study, regarding ␤-receptor binding in the lung, there was a greater effect in males than females (62).…”
Section: Discussionmentioning
confidence: 99%
“…A further potential mechanism regulating changes in the fetal lung following exposure to hyperglycemia and hyperinsulinemia involves ␤-receptor binding, which plays a vital role in surfactant release and reabsorption of fetal lung liquid (62,64). Interestingly, although the latter study demonstrated a negative impact of hyperglycemia and hyperinsulinemia, similar to that experienced in this study, regarding ␤-receptor binding in the lung, there was a greater effect in males than females (62). This represents a potential mechanism for male infants to suffer disadvantage in respiratory morbidity following exposure to uncontrolled diabetes during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation